Hubungan Pengetahuan,Sikap,Tingkat Konsumsi Energi, Protein, dan Indeks Massa Tubuh/Umur dengan Kekurangan Energi Kronik pada Remaja Putri (Studi di Sekolah Menengah Kejuruan Islamic Centre Baiturrahman Semarang pada Puasa Ramadhan Tahun 2017) - Agustin Dwi Arista; Laksmi Widajanti; Ronny Aruben (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Chronic Energy Deficiency (CED) is a condition where adolescent girls or women are having nutritional deficiency (energy and protein) which occurs for a long time or even years. CED risk is a condition where adolescent girls/women have a tendency to suffer from CED. Someone is diagnosed having CED risk is when the mid-upper arm circumference < 23,5 cm. The purpose of this research was to analyze the correlation of knowledge, attitude, level of energy consumption, protein and Body Mass Index for Age with CED risk in adolescent girl in Islamic Centre Baiturrahman Vocational High School Semarang on Ramadhan fasting 2017. This was a quantitative research with cross sectional design study. Population of this research were 87 adolescent girls in grade XI. Samples of this research were 46 adolescent girls who meet the inclusion criteria. Sampling technique was using purposive sampling. Data was analyzed using Rank Spearman. The results showed that average of respondents’ knowledge about nutrition 57.5% score. Median score of respondents’ attitude about nutrition 58.5% positive attitude. Median score of respondents’ level of energy consumption 55.0% RDA. Median score of respondents’ level of protein consumption 62.17% RDA. The average of respondents’ Body Mass Index for Age -0.3135. Statistical trial showed that there were no correlation of knowledge with CED (p=0,631), attitude with CED (p=0,251), level of energy consumption with CED (p=0,545), and level of protein consumption with CED (0,052). There was a correlation of Body Mass Index for Age with CED (p=0,000). This research suggested adolescent girls to increase nutritional intake as needed in order to prevent CED in the future.